Novel 2D Graphic Representation of Protein Sequence and Its Application (Journal of Fiber Bioengineering and Informatics, 2014)
In recent years, more and more researchers presented their graphic representations for protein sequence.Here, we present a new 2D graphic representation of protein sequence based on four physicochemicalproperties of 20 amino acids. By this graphic representation we define a distance calculation formulato quantificationally calculate the similarity degree of different protein sequences. Then we apply theproposed graphical curve and new distance in the similarity/dissimilarity comparison of 10 ND5 proteinsand the protein sub-cellular localization prediction about two common test datasets, ZD98 and CL317.The results show the proposed method is easy and effective.